Anticancer and Health Promoting Components in Citrus Fruit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Cancers, cataract and cardiovascular diseases are commonly recognized as degenerative diseases as they usually develop with aging. Accumulated evidences from experimental and epidemiological studies indicate that there is a low risk of these degenerative diseases in people with high intake of fruits and vegetables. This protective effect is assumed to be associated mainly with the antioxidant activity of either individual or interactions among bioactive components present in the fruits and vegetables and with other biochemical and physical characteristics of the identified and unknown components. High intake of citrus fruits may reduce the degenerative diseases, and the implicated bioactive components present in citrus fruits include vitamin C, fl-carotene,lavonoids, limonoids, folic acid, and dietary fibre. This paper presents a review on the degenerative diseases protective activity of these bioactive components